2009
DOI: 10.1007/s11274-009-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyhydroxyalkanoate and the phaC gene of Paracoccus seriniphilus E71 strain isolated from a polluted marine microbial mat

Abstract: Polyhydroxyalakanote (PHA) was produced by the marine bacteria Paracoccus seriniphilus Strain E71. Three methods were used for screening PHA in this strain:(1) microscopic analysis, (2) specifically designed primers for amplify fragments of phaC gene from Gram negative bacteria, and (3) measurements using spectroscopy, calorimetry, thermogravimetry, and rheology. The polyhydroxyalkanoic acid synthase gene (phaC) sequence had 77% identity with the phaC gene of P. denitrificans PD1222 strain. Additionally, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Likewise, Barbosa et al (2005) and Hong et al (1999) reported that 2928 cm −1 bands corresponded to C H group vibrations or extensions for PHB and PHAs obtained from fructose and different cell types. Lopez-Cortes et al (2010), Lopez-Cuellar et al, 2011;and Misra et al (2000) reported that the 1724 cm −1 band was the C O extension, which was to what was found in this investigation. Moreover, asymmetric CH bending, found in this study at 1452-1457 cm −1 and 1379-1384 cm −1 , corresponded to CH 2 and CH 3 groups, respectively, and was also reported by Oliveira et al (2007) and Gáscue et al (2000).…”
Section: Infrared Spectroscopy Analysissupporting
confidence: 89%
“…Likewise, Barbosa et al (2005) and Hong et al (1999) reported that 2928 cm −1 bands corresponded to C H group vibrations or extensions for PHB and PHAs obtained from fructose and different cell types. Lopez-Cortes et al (2010), Lopez-Cuellar et al, 2011;and Misra et al (2000) reported that the 1724 cm −1 band was the C O extension, which was to what was found in this investigation. Moreover, asymmetric CH bending, found in this study at 1452-1457 cm −1 and 1379-1384 cm −1 , corresponded to CH 2 and CH 3 groups, respectively, and was also reported by Oliveira et al (2007) and Gáscue et al (2000).…”
Section: Infrared Spectroscopy Analysissupporting
confidence: 89%
“…To obtain a prime region of phaC gene from the potent PHA producing strain, two degenerated primers reported by López-Cortés et al (2010) were used. PCR conditions for amplification of a region belonging to the phaC gene are given in MMS 6.…”
Section: Detection Of Phac Genementioning
confidence: 99%
“…Moreover, PHB-producing bacilli are capable of rapid growth on a variety of cost-effective substrates, while gram-negative bacteria require expensive substrates which should be structurally related substrate to produce the PHAs polymer. Therefore, large numbers of bacilli are used in PHAs production and recommended for biomedical applications (Chen et al, 1991;Wu et al, 2001;Yilmaz et al, 2005;Valappil et al, 2007;Singh et al, 2009;Lopez-Cortes et al, 2010;Mizuno et al, 2010).…”
Section: Discussionmentioning
confidence: 99%